Collision-induced stimulated photon echo in magnetic field. (29th October 2015) - Reshetov, V A
Abstract: The action of the longitudinal magnetic field on the collision-induced stimulated photon echo formed on the transition with the angular momentum change is studied theoretically. It is shown that this action depends essentially on the sign of the difference in the orientation and alignment relaxation rates of the excited level b . If, then the echo intensity in a weak magnetic field increases with the increase in the magnetic field strength, while in the alternative case it decreases up to zero value. The formulae enabling the determination of the magnitude of the difference from the experimental study of the oscillations of the echo intensity with the increase in the magnetic field strength are obtained.